Funding linked to ongoing research: Impact of the bosentan patient registry on pricing in Australia - Wlodarczyk, J.; Reid, Christopher; Pater, G. (2011)
Objectives: Bosentan, a dual endothelin receptor antagonist (ERA), was the first oral drug approved for the treatment of pulmonary arterial hypertension (PAH), a rare disease with poor prognosis. In 2004 the Australian Department of Health agreed to fund bosentan on the pharmaceutical benefits scheme (PBS) on the condition that a registry was established to monitor mortality: if the observed mortality rate was higher than that claimed in the original funding submission then the price of bosentan would be reduced to maintain the original incremental cost-effectiveness ratio (ICER). This article presents the economic implications of the bosentan patient registry (BPR). Methods: An existing economic model was updated using the results of the BPR. Results: Participation rates were high and the BPR collected 821 patient years of follow-up on 528 patients. Based on the observed raw mortality a 23.7% price reduction would have been needed to maintain the original ICER in idiopathic PAH patients. After allowing for the higher risk patients actually treated in Australia, a 13.5% reduction in bosentan price would have been required. In 2008, however, sitaxentan, a new oral ERA PAH treatment was listed on the PBS at a 15% discount to bosentan. On the basis of cost-minimization, bosentan was forced to reduce its price to that of sitaxentan. After this price reduction the ICER for bosentan was similar to that originally proposed and hence, no additional price reduction was sought by the Pharmaceutical Benefits Advisory Committee (PBAC). Conclusions: The bosentan PAH registry provided a useful mechanism for monitoring the cost-effectiveness of bosentan after funding approval. © 2011 International Society for Pharmacoeconomics and Outcomes Research (ISPOR).